2009
DOI: 10.1523/jneurosci.3641-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Combining Peripheral Nerve Grafts and Chondroitinase Promotes Functional Axonal Regeneration in the Chronically Injured Spinal Cord

Abstract: Because there currently is no treatment for spinal cord injury, most patients are living with long-standing injuries. Therefore, strategies aimed at promoting restoration of function to the chronically injured spinal cord have high therapeutic value. For successful regeneration, long-injured axons must overcome their poor intrinsic growth potential as well as the inhibitory environment of the glial scar established around the lesion site. Acutely injured axons that regenerate into growth-permissive peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 56 publications
7
130
1
1
Order By: Relevance
“…These results are consistent with previous studies, which have shown axons growing through the distal interface of the PNG [16][17][18].…”
Section: Induced Functional Recovery After Complete Spinal Cord Injurysupporting
confidence: 94%
See 4 more Smart Citations
“…These results are consistent with previous studies, which have shown axons growing through the distal interface of the PNG [16][17][18].…”
Section: Induced Functional Recovery After Complete Spinal Cord Injurysupporting
confidence: 94%
“…It is well documented that regeneration of injured axons after an acute or chronic SCI can be facilitated by the application of ChABC [8,18]. In this study, we did have more functional recovery in the ChABC treated rats, although it was not always significant.…”
Section: Opf Tubes For Chabc Deliverycontrasting
confidence: 41%
See 3 more Smart Citations